(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The article deals with the concept of a political institution in its historical origin and development. A political institution is a kind of composite value in the state, forming its main authorities. In the historical context, most political scientists and sociologists have not directly singled out a political institution as something separate from the state. Only by the beginning of the 20th century did a clearer definition of a political institution appear and develop. And already modern researchers are considering a political institution, which is a set of political and economic organizations, of which not all are state-owned. The author argues that the development of political institutions within the state affects the strengthening of the system of "checks and balances", which makes the functioning of the state more successful. In addition, the author believes that the concept of a political institution is becoming "blurred" in modern research circles and requires a larger study to determine the essence of a political institution.